Do Abnormally High Audit Fees Impair Audit Quality? - Choi, Jong-Hag; Kim, Jeong-Bon; Zang, Yoonseok (Auditing : a journal of practice and theory, 2010)
This study examines whether and how audit quality proxied by the magnitude of absolute discretionary accruals is associated with abnormal audit fees, that is, the difference between actual audit fee and the expected, normal level of audit fee. The results of various regressions reveal that the association between the two is asymmetric, depending on the sign of the abnormal audit fee. For observations with negative abnormal audit fees, there is no significant association between audit quality and abnormal audit fee. In contrast, abnormal audit fees are negatively associated with audit quality for observations with positive abnormal audit fees. Our findings suggest that auditors’ incentives to deter biased financial reporting differ systematically, depending on whether their clients pay more than or less than the normal level of audit fee. Our results are robust to a variety of sensitivity checks.